Pack-boriding of AISI P20 steel: estimation of boron diffusion coefficients in the Fe2B layers and tribological behaviour. (2017) - Keddam, M.; Elias-Espinosa, M.; Ortiz-Domínguez, M.; Simón-Marmolejo, I.; Zuno-Silva, J.
In the present study, the AISI P20 steel was pack-borided in the temperature range of 1, 123-1, 223 K for treatments times between 2 and 8 h. A new kinetic model based on the integral method was used to estimate the boron diffusion coefficients in the Fe2 B layers. As a result, the activation energy for boron diffusion in the AISI P20 steel was estimated as 194.3 kJ mol −1 . This value of energy was compared with the literature results. Furthermore, to validate experimentally the present model, two additional boriding conditions were used. The morphology of cross-sections of borided samples was examined by scanning electron microscopy. The formation of a single boride layer was confirmed by x-ray diffraction analysis. The Daimler-Benz Rockwell-C indentation technique was used to evaluate the cohesion of boride layers on the surface of AISI P20 steel. Finally, the scratch and pin-on-disc tests for wear resistance were carried out by means of a LG Motion Ltd and a CSM tribometer respectively under dry sliding conditions.